Effects of alternating heat and cold stimulation at different cooling rates using a wearable thermo device on shoulder muscle stiffness: a cross-over study - Tomonori Sawada; Hiroki Okawara; Daisuke Nakashima; Shuhei Iwabuchi; Morio Matsumoto; Masaya Nakamura; Takeo Nagura (BMC Musculoskeletal Disorders, 2022)
Abstract Background A small, wearable thermo device that uses Peltier elements for programmed heat and cold stimulation has been developed recently and is expected to be applied in conventional contrast bath therapy. This study was aimed to examine improvements in trapezius muscle hardness and subjective symptoms resulting from alternating heat and cold stimulation, with different rates of cooling. Methods This cross-over study included four conditions. Twenty healthy young male individuals (age, 22.3 ± 4.5 years) participated in this study. These four interventions targeted the unilateral trapezius muscle of the dominant arm after a 15-min typing task. Specifically, heat and cold stimulations were applied at different ratios (the heating/cooling rate of 3:1, 3:2, and 3:3) or not applied. Each intervention was separated by at least one week. Skin temperature at the stimulation area was recorded using a data logger. Outcome measures included muscle hardness (measured using a portable tester) and subjective symptoms (muscle stiffness and fatigue). Each item was assessed at three time points: baseline, after typing, and after the intervention. Results Two-way analysis of variance with repeated measures found an interaction effect for muscle hardness between four conditions (3:1, 3:2, 3:3, and no) and three time points (p < 0.05). Only in the 3:1 condition were the post-intervention values lower than those after typing (p < 0.01). There was also an interaction effect for subjective muscle stiffness (p < 0.05); the values after the intervention in the 3:1 condition were lower than those after intervention in the no stimulation condition (p < 0.01). There was no significant relationship between changes in muscle hardness and changes in subjective symptoms in the 3:1 condition. Conclusions Our results demonstrate that alternating heat and cold stimulations with a different cooling rate could affect the degree of improvement in muscle hardness and subjective symptoms. In particular, the 3:1 condition has the possibility to improved muscle hardness within the condition and subjective muscle stiffness between conditions. Trial registration UMIN000040620. Registered 1 June 2020, https://upload.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000046359